(untitled) (American Journal of Pedagogical and Educational Research, 2024)
The article deals with the role of national values in the upbringing of children and youth is invaluable. The paper describes the meaning and essence of the word value. It is stated that value is a set of factors that are manifested in natural and social life, appreciated by people, useful, significant, material, economic, spiritual, cultural, ideological, political, legal, religious, national, and social.